Модель сенсорной системы автономного мобильного робота-промоутера - Пономарева, А. В.; Логвиненко, Т. Н.; Дерюгина, Е. С. (ДонНТУ, 2017)
Предложен проект сенсорной системы, которая реализует многоуровневое получение информации. Нижний уровень предназначен для обнаружения преград при осуществлении перемещения робота. Верхний уровень – для поиска объектов и выполнения функции взаимодействия с людьми.
A project of a sensory system that implements multi-level information acquisition is proposed. The lower level is designed to detect obstacles when moving a robot. The upper level is for searching for objects and performing the function of interaction with people. Key words: robot, sensor, system.
Keywords: мобільні роботи; сенсорні системи; роботи-промоутери